Marx: alienation, commodity fetishism and the world of contemporary social work. (28th August 2018) - Lavalette, Michael; Ferguson, Iain
Abstract : This article offers an outline of Marx's concept of alienation and his later related concept of commodity fetishism. Building on previously published work on this topic, we argue that the lack of control over our lives and creative activity that, for Marx, defined alienation and that he saw as being more extreme under capitalism than under any previous mode of production has actually intensified during the era of neoliberalism. Through an examination of the areas of work, sexuality and health, we examine the terrible toll that the lack of control and greatly increased commodification is having on our health and relationships. Finally, we point to some ways in which an understanding of alienation can contribute to a radical social work theory and practice.